Social Distrust Impact Analysis: Political Overview Competition Law - Israhadi, Evita Isretno (International Journal of Criminology and Sociology, 2021)
The purpose of this research is to reveal the contents of civil law regarding business competition and social lessons from the prohibition of unfair business competition (monopoly and other fraud) contained in Indonesian government policies. The research method used is qualitative content analysis with a normative juridical approach using the keyword ’Policy related to business competition.’ The results of this study indicate two findings. First, Law No. 5/1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition is an implementation of the politics of business competition law in Indonesia. In principle, the politics of business competition law in Indonesia depends on the political will of the House of Representatives (DPR) as the legislative body together with the Government as the executive in making laws. Because Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition is not yet effective enough in creating fair business competition in Indonesia because, in substance, the Law still contains weaknesses in several articles that make the performance of the Business Competition Supervisory. The commission is not maximal. Second, government policies contained in the Civil Code, KUHP, Law no. 5 of 1984 concerning Provisions for Main Industries, Law no. 8/1995 concerning Capital Market, Law no. 9 of 1995 concerning Small Businesses, and Law No. 36 of Telecommunications provide important lessons regarding the prohibition of monopolies and fraudulent practices that can hinder the economy and equitable social welfare. The expected implication is that social learning from government policies in the field of law regarding deregulation, investment, and other policies aimed at supporting business competition can promote sustainable development, particularly in industry, small businesses, capital markets, and telecommunications.